2019
DOI: 10.1080/09638288.2019.1668486
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric tumor location and the impact on health-related quality of life, symptomatology, and functional performance outcomes in patients with glioma: an exploratory cross-sectional study

Abstract: To inform high-quality rehabilitation services, this study investigates if patients with glioma located in the right-or lefthemisphere present with different health-related quality of life, symptomatology, and functional performance in the early disease state. Material and methodsBetween 2013 and 2017, 81 adult patients were assessed during the first week of chemo-radiation, following resection.Patients were stratified into two groups depending on a right-or left-hemispheric lesion. Independent t-tests analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…In newly diagnosed high-grade glioma patients, Klein et al [29] found that although tumor lateralization was significantly correlated self-reported difficulties in specific neurocognitive functions such as reasoning, problem-solving, reaction time, forgetfulness, and concentration, two higher-order HRQoL component scores (physical component scale, mental component scale) did not depend on the side of the affected hemisphere. Several other studies have also not shown any prominent differences in overall HRQoL between left-and right-sided brain tumors in the preoperative or early postoperative phase [34][35][36]. However, as expected, patients with left-sided tumors reported suffering more often from disturbances in verbal fluency, verbal learning, memory problems, and communications deficits, while tumors in the right hemisphere caused greater difficulties in process skills when performing everyday tasks [35,36].…”
Section: Interaction Between Glioma Laterality and Health-related Qua...mentioning
confidence: 55%
See 1 more Smart Citation
“…In newly diagnosed high-grade glioma patients, Klein et al [29] found that although tumor lateralization was significantly correlated self-reported difficulties in specific neurocognitive functions such as reasoning, problem-solving, reaction time, forgetfulness, and concentration, two higher-order HRQoL component scores (physical component scale, mental component scale) did not depend on the side of the affected hemisphere. Several other studies have also not shown any prominent differences in overall HRQoL between left-and right-sided brain tumors in the preoperative or early postoperative phase [34][35][36]. However, as expected, patients with left-sided tumors reported suffering more often from disturbances in verbal fluency, verbal learning, memory problems, and communications deficits, while tumors in the right hemisphere caused greater difficulties in process skills when performing everyday tasks [35,36].…”
Section: Interaction Between Glioma Laterality and Health-related Qua...mentioning
confidence: 55%
“…Several other studies have also not shown any prominent differences in overall HRQoL between left-and right-sided brain tumors in the preoperative or early postoperative phase [34][35][36]. However, as expected, patients with left-sided tumors reported suffering more often from disturbances in verbal fluency, verbal learning, memory problems, and communications deficits, while tumors in the right hemisphere caused greater difficulties in process skills when performing everyday tasks [35,36]. These results suggest that measures of global health should be interpreted with caution, as this scale may be insensitive to detect changes over time or between groups.…”
Section: Interaction Between Glioma Laterality and Health-related Qua...mentioning
confidence: 90%
“…In newly diagnosed high-grade glioma patients, Klein et al [26] found that although tumor lateralization signi cantly affected self-reported di culties in speci c neurocognitive functions such as reasoning, problem-solving, reaction time, forgetfulness, and concentration, two higherorder QoL component scores (physical component scale, mental component scale) did not depend on the side of the affected hemisphere. Several other studies have also not shown any prominent differences in overall QoL between left-and right-sided brain tumors in the preoperative or early postoperative phase [31][32][33]. However, as expected, patients with left-sided tumors reported suffering more often from disturbances in verbal uency, verbal learning, memory problems, and communications de cits, while tumors in the right hemisphere caused greater di culties in process skills when performing everyday tasks [32,33].…”
Section: Impact Of Glioma Laterality On Quality Of Lifementioning
confidence: 58%
“…Several other studies have also not shown any prominent differences in overall QoL between left-and right-sided brain tumors in the preoperative or early postoperative phase [31][32][33]. However, as expected, patients with left-sided tumors reported suffering more often from disturbances in verbal uency, verbal learning, memory problems, and communications de cits, while tumors in the right hemisphere caused greater di culties in process skills when performing everyday tasks [32,33].…”
Section: Impact Of Glioma Laterality On Quality Of Lifementioning
confidence: 58%
“…All 34 included articles were published between 1998 and 2022, consisting of 16 cross-sectional studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], 7 randomised control trials (RCT) [30][31][32][33][34][35][36], 4 quasi-experimental studies [37][38][39][40], and 7 cohort studies [41][42][43][44][45][46][47]. The results of the included articles were informed by 4,694 PBT survivors and 120 caregivers, with sample sizes ranging from 12 to 621 with an age range of 18-86 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%